PW 1685 Community based epidemiological study of road traffic injuries in delhi. (November 2018) - Verma, Pramod Kumar; Verma, Eshant
Abstract : Background: Road traffic injury has multi-factorial etiology and epidemiological study can solve its complexity for planning of preventive strategies. We cannot directly adopt research carried out in developed countries where circumstances of injury vary from developing countries. Therefore, WHO, SEARO sponsored this study. Objectives: To find various epidemiological factors of road traffic injuries. Methods: This is a retrospective one-year descriptive epidemiological study of various types of injuries among 30 554 population of Delhi. Findings: Among 30 554 population, there were 680 traffic injuries with (IR) 22.3 per 1 000 population. 69% occurred in age group of 15 to 35 years. Male:female ratio was 4:1. The IR was more in business group(44.0) followed by the service group (40.1), labour group(28.9). IR was more among 6–8 class education(5.3), followed by graduates(3.6). Limbs(62.2%) were the most affected part followed by head injury (11.2%). Superficial injuries were most common(47.4%), followed by fractures(20.7%), crush injuries(14.1%) and concealed injuries(12.4%). 19.3% injuries occurred during recreational activity. Majority of the injured victims (92.4%) treated within 6 hours while 70.0% treated within 1 hour. 44.4% treated at nearby clinic and 26.8% at government hospitals and 16% at private hospitals. 47.1% treated at OPD; 5.9% hospitalized; 9% were critically ill, 1.8% were operated upon, and 1.3% had to be admitted in ICU. 19.3% resumed work within 2–4 days of injury, followed by 14.7% within 5–7 days while 13.4% could not resume normal work for 1–2 months. 46.3% used two-wheelers transport and 24.8% were pedestrians. Conclusion: Incidence was more among young adult male, low education and limb was most affected and used 2-wheeler as transport for treatment at nearby clinic Policy implication: Preventive strategic planning must be based on epidemiological factors.